2005
DOI: 10.1111/j.1523-1755.2005.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiproteinuric effect of oral paricalcitol in chronic kidney disease

Abstract: Our results demonstrate that the reduction in proteinuria was associated with paricalcitol treatment, and the reduction in proteinuria was independent of concomitant use of agents that block the RAAS. Paricalcitol as a potential pharmacologic means of reducing proteinuria in CKD patients warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
214
4
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(227 citation statements)
references
References 26 publications
(26 reference statements)
4
214
4
5
Order By: Relevance
“…A delayed and less intense rise of albumin excretion was achieved with R-568 and calcitriol, consistent with previous findings in experimental studies (17,19) and clinical observations (2).…”
Section: Discussionsupporting
confidence: 81%
“…A delayed and less intense rise of albumin excretion was achieved with R-568 and calcitriol, consistent with previous findings in experimental studies (17,19) and clinical observations (2).…”
Section: Discussionsupporting
confidence: 81%
“…However, four RCTs showed that a number of patients had a reduction in proteinuria. 25) provided the data on albuminuria before and after paricalcitol treatment. Therefore, we used a reduction in proteinuria .10% from baseline value as our study end point.…”
Section: Effects On Proteinuriamentioning
confidence: 99%
“…Four studies of nine RCTs were undertaken to prospectively test the effectiveness of paricalcitol in reducing of residual albuminuria in a total of 469 patients with CKD who were receiving stable treatment with an angiotensinconverting enzyme (ACE) inhibitor or an angiotensin receptor blocker (ARB) (9,(25)(26)(27). In these studies, 285 patients were assigned to the treatment groups and 184 patients received placebo.…”
Section: Effects On Proteinuriamentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that pleitropic effects of vitamin D go beyond bone and mineral metabolism and the activity of parathyroid glands, thus being possibly related to other potential areas of CKD. It has been demonstrated that vitamin D supplementation has an antiproteinuric effect, 33 to regulate the reninangiotensin-aldosterone, 34 , to reduce histological changes found in glomerulosclerosis, 35 , and, finally, to reduce CKD progression. 4 To sum up even if our population with CKD is in a tropical environment, which leads to more exposure to the sun and, consequently, a higher production and serum levels of 25(OH)D, our study showed that most analyzed patients had serum levels of 25(OH)D below recommended values, especially lower among women and in patients with larger abdominal circumference.…”
Section: Discussionmentioning
confidence: 99%